Kinerja Pegawai Ditinjau dari Perceived Organizational Support, Kompensasi, Organizational Citizenship Behavior, Lingkungan Kerja, dan Stres Kerja pada Instalasi Radiologi RSUD Dr. Moewardi - Eka Sulistiya; Istiatin; Sudarwati (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
Performance data from 2022 to 2024 indicates that employee performance in 2024 is less than optimal, with a downward trend. This phenomenon prompted an evaluation by examining five determinants that influence employee performance. This quantitative research aims to examine the effects of POS, compensation, OCB, work environment, and job stress on employee performance. The Radiology Unit of Dr. Moewardi Regional Hospital was used as the research object, and this census study used a sample of 45 employees. Data were collected through questionnaires, with multiple linear regression data analysis. The research results showed that POS, compensation, OCB, and work environment had a significant effect on performance, but job stress was not proven to affect employee performance.